Male Infertility in Libyan Arab Jamahiriya (Bangladesh Journal of Medical Science, 2014)
Male infertility is also an important social problem. 160 male subjects were examined in Libya. 90.00% subjects were between the age of 20-30 years. Out of 160 male, 60 (37.50%) were normospermic, 60 (37.53%) oligospermic, 28 (17.50%) azoospermic and 12 (7.5%) were necrospermic. So, 63.50% subjects had fertility problem.DOI: http://dx.doi.org/10.3329.bjms.v1i3.17910